Upper body subcutaneous adipose as a potential predictor for type 2 diabetes mellitus - Scepanovic, Andjelka; Vujovic, Slavica; Medin, Darko (Progress in Nutrition, 2019)
Background/Aim: Upper body skinfold measurements show association with type 2 diabetes mellitus (DM2). Precise predictive potential of the various points of the subcutaneous adipose tissue thickness in the upper body is not completely defined. The aim of this study was to examine the predictive potential of 4 subcutaneous fatty tissue spots (i.e., biceps, triceps, abdominal and subcapsular) regarding DM2 subjects diagnosed with disease before 60 years of age. Methods: Subcutaneous fatty tissue points were measured by a caliper in 108 subjects with DM2 who were diagnosed with the disease before the 60 years of age and compared with the same points of subcutaneous adipose tissue thickness of 112 control group subjects. Results: Skinfold measurments parameters were higher in DM2 subjects compared to controls (p <0,05). Female subjects with DM2 had significantly higher skinfold measurements (19,85±0,99 mm compared to 14,90 ± 0,61 mm, p <0,001 for Biceps and 29,09 ± 1,20 mm compared to controls, 22,00 ± 1,00 mm for Triceps). Abdominal and subscapular SAT measurements were higher in female DM2 group compared to controls 34,53 ± 0,99 mm compared to 27,72 ±1,08 mm and 33,53 ± 1,07 mm compared to 26,00 ± 1,18 mm with p <0,001, respectively, while no significant difference was found in male subjects (p >0,05). Upper body skinfold measurement values were found to be predictors for DM2 and they more significant in female subjects with OR values of 1,139 for biceps, 1,091 for triceps, 1,099 for abdominal and 1,088 for subscapular spot, while they were found to be less significant in male subjects (p >0,05). Body mass index and waist circumference were also shown to be significant predictors for DM2 in female subjects (p <0,05). Conclusion: Subcutaneous fatty tissue of the upper body has a great predictive potential when it comes to DM2, especially in women